the role of arbuscular mycorrhiza in the biological control of Fusarium oxysporum in tomato - Pinto, José Tomás Madeira (2020)
The functional diversity amongst arbuscular mycorrhizal fungi (AMF) is scientifically recognized, yet not practically exploited as the understanding of the interactions between different crops and their rhizosphere microbiome is still very narrow. Following the strategy developed by the team that guided this dissertation, this work was aimed to test different plants (Lolium rigidum and Ornithopus compressus) as hosts to develop AMF extraradical mycelium (ERM) for an early colonization of tomato plants and to evaluate their role in the bioprotection against Fusarium oxysporum f. sp radicis-lycopersici. Although L. rigidum promoted a greater AM colonization of tomato plants, O. compressus was most beneficial, resulting in a reduced disease incidence and a higher dry weight in the tomato plants. The disease incidence was also lower in undisturbed soil (intact ERM) conditions, confirming the importance of an early AM colonization, accomplished through an intact ERM, in granting bioprotection to the tomato plants; O papel das micorrizas arbusculares no controlo biológico de Fusarium oxysporum em tomate Resumo: Apesar da diversidade funcional entre fungos micorrízicos arbusculares (AMF) estar cientificamente descrita, o conhecimento do microbioma rizosférico das culturas é ainda bastante limitado e a sua utilização em termos práticos está ainda longe de ser uma realidade. Seguindo a estratégia desenvolvida pela equipa que acolheu esta dissertação, este trabalho visou testar plantas (Lolium rigidum e Ornithopus compressus) como hospedeiros para desenvolver micélio extraradicular (ERM) de AMF, para obter uma colonização precoce nos tomateiros e avaliar o seu papel na bioprotecção contra Fusarium oxysporum f. sp. radicis-lycopersici. Apesar do L. rigidum ter promovido uma colonização micorrízica superior nos tomateiros, o O. compressus foi mais benéfico, resultando numa redução de incidência da doença e num aumento do peso seco dos tomateiros. A incidência da doença foi menor em condições de solo não perturbado (ERM intacto), confirmando a importância da colonização micorrízica precoce, obtida a partir de ERM intacto, no efeito bioprotector a tomateiros.